Joyous Garde
Aroynt' threshhold (Aroynt is Middle English for 'begone') at the entrance to Geoyous/Joyous Garde, Steinbeck's hexagonal writing room, which looked out over cove near Bluff Point in Sag Harbor, New York. Added in 1958, when the room was built, and it refers to the reason Steinbeck had the office built; for privacy from guests and family. Color.